2008
DOI: 10.1088/0031-9155/53/12/010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3D-OP-OSEM and 3D-FBP reconstruction algorithms for High-Resolution Research Tomograph studies: effects of randoms estimation methods

Abstract: The High-Resolution Research Tomograph (HRRT) is a dedicated human brain positron emission tomography (PET) scanner. Recently, a 3D filtered backprojection (3D-FBP) reconstruction method has been implemented to reduce bias in short duration frames, currently observed in 3D ordinary Poisson OSEM (3D-OP-OSEM) reconstructions. Further improvements might be expected using a new method of variance reduction on randoms (VRR) based on coincidence histograms instead of using the delayed window technique (DW) to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…For the Hoffman phantom decay study, ANW-OSEM performed poorly, with a change in the GM-to-WM contrast ratio of 20%. In a previous study (9), we reported a high-contrast change in the GM-to-WM contrast ratio (54%) using the manufacturer's implementation of OP-OSEM. Using the in-house-implemented OP-OSEM with the same convergence criteria, the same ROI definitions, and the same scan of the Hoffman phantom, we obtained a good (and stable) GM-to-WM contrast ratio (10%), as we did with most other reconstruction methods (between 8% and 10%).…”
Section: Phantom Studiesmentioning
confidence: 92%
See 3 more Smart Citations
“…For the Hoffman phantom decay study, ANW-OSEM performed poorly, with a change in the GM-to-WM contrast ratio of 20%. In a previous study (9), we reported a high-contrast change in the GM-to-WM contrast ratio (54%) using the manufacturer's implementation of OP-OSEM. Using the in-house-implemented OP-OSEM with the same convergence criteria, the same ROI definitions, and the same scan of the Hoffman phantom, we obtained a good (and stable) GM-to-WM contrast ratio (10%), as we did with most other reconstruction methods (between 8% and 10%).…”
Section: Phantom Studiesmentioning
confidence: 92%
“…Further improvements were expected by using the VRR algorithm (5), which estimates expected randoms (v i ) from measured delayed coincidences (9). The mathematic formulae are the same, except that v i is used instead of d i, and the trues (t i ) are calculated by p i 2 v i .…”
Section: Reconstruction Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24 Nevertheless, noise reduction with a better TOF resolution (i.e., better effective sensitivity) and running lower number of OSEM updates was demonstrated to be able to minimize the bias in both µ-map and emission image as expected. Based on these results, the new generation of TOF PET scanners which employ digital PET detectors with 300-400 ps TOF resolution is expected to improve the accuracy of the proposed method at low count situations.…”
Section: Discussionmentioning
confidence: 63%